1996
DOI: 10.1093/oxfordjournals.humrep.a019373
|View full text |Cite
|
Sign up to set email alerts
|

The development of mouse zygotes after fusion with synchronous and asynchronous cytoplasm

Abstract: Cytoplasts with diameters of 40-45, 50-55 and 70-75 microm, derived from mouse oocytes at the germinal vesicle, metaphase II and zygote stages were incorporated into zygotes by electrofusion. Manipulated (n = 867) and culture-control (n = 1114) embryos were cultured in vitro and transferred to pseudo-pregnant recipients at the blastocyst stage. When synchronous cytoplasts measuring 40-45 and 50-55 microm in diameter were incorporated into 138 and 86 zygotes respectively, only one embryo in each group (not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…However, there have been strong controversies related to using ICSI as a human therapeutic technique. The quality of the embryos obtained after ICSI could not be correlated with the previous observations gathered from regular IVF, where there was a strong negative relationship between embryo quality and abnormal sperm parameters (2)(3)(4)(5).…”
Section: Their Previous In Vitro Fertilization (Ivf) Cycle(s)contrasting
confidence: 66%
“…However, there have been strong controversies related to using ICSI as a human therapeutic technique. The quality of the embryos obtained after ICSI could not be correlated with the previous observations gathered from regular IVF, where there was a strong negative relationship between embryo quality and abnormal sperm parameters (2)(3)(4)(5).…”
Section: Their Previous In Vitro Fertilization (Ivf) Cycle(s)contrasting
confidence: 66%
“…Low mitochondrial DNA content has been reported to occur more frequently in women with ovarian insufficiency than in those with normal ovarian function (May-Panloup et al ., 2005). The consequences of impaired mitochondrial function in human oocytes are currently unknown, but animal studies have shown that replacement of ooplasm in ooplasmic-deficient eggs will restore their developmental capacity (Levron et al ., 1996). The observed high rate of pregnancy loss in women with reduced ovarian reserve (evidenced by elevated basal FSH levels) indirectly supports the notion of a qualitative reduction in oocyte quality (Levi et al ., 2001).…”
Section: Individualized Ovarian Stimulationmentioning
confidence: 99%
“…Germinal vesicle (GV) transfer techniques have represented useful tools for studying the interaction between the nucleus and the cytoplasm in the oocyte maturation process in mammals (Chiang et al, 2012;Cohen et al, 1997;Dekel and Beers, 1978;Fulka et al, 1998Fulka et al, , 2001Heacox and Schroeder, 1981;Levron et al, 1996;Li et al, 2001;Liu et al, 1999Liu et al, , 2000Zhang et al, 1999). Furthermore, GV transfer between different mammalian species has demonstrated that cytoplasmic factors regulating the progression of the first and the second meioses are not species-specific in mammalian oocytes and that these factors are located in the meiotic apparatus and/or its surrounding cytoplasm at the MII stage (Li et al, 2001).…”
Section: Introductionmentioning
confidence: 99%